Dictionary of international banking and finance terms - Clark, John Owen Edward; Clark, John Owen Edward; Financial World Publishing (Canterbury, Kent, United Kingdom : Financial World Pub., 2001)
Over 4,000 terms defined in the fields of retail and wholesale banking. Up to date with the regulatory environment, EMU as well as products and services provided through the increasing use of technology by financial services companies. It includes procedures and documentation in use in both front and back office functions and all international bodies.
Rev. ed. of: International dictionary of banking and finance / John Clark. c1999.
oif 08/02/2019
Ref.
Keywords: International finance; Dictionary - international banking; Banks and banking, International; Finance; Banks and banking